A Health Technology Assessment of Transient Elastography in Adult Liver Disease. (2013) - Steadman, Rodney; Myers, Robert P; Leggett, Laura; Lorenzetti, Diane; Noseworthy, Tom; Rose, Sarah; Sutherland, Lloyd; Clement, Fiona
Abstract : BACKGROUND: An estimated one in 10 Canadians have some form of liver disease. The reference standard for staging and monitoring liver fibrosis is percutaneous liver biopsy – an invasive procedure associated with risks and complications. Transient elastography (TE) represents a noninvasive, ultrasound-based alternative. OBJECTIVE: To assess the efficacy of TE compared with liver biopsy for fibrosis staging in adults with five common types of liver disease: hepatitis B, hepatitis C, nonalcoholic fatty liver disease, cholestatic liver disease and complications post-liver transplantation. METHODS: A systematic review of published and grey literature from 2001 to June 2011 was conducted. Included were observational studies evaluating the accuracy of TE using liver biopsy as the comparator. An economic model was developed to estimate the cost per correct diagnosis gained with liver biopsy compared with TE. Identification of moderate fibrosis (stages 2 to 4) and cirrhosis (stage 4) were considered. RESULTS: Fifty-seven studies were included in the review. The diagnostic accuracy of TE for the five clinical subgroups had sensitivities ranging from 0.67 to 0.92 and specificities ranging from 0.72 to 0.95. Liver biopsy was associated with an additional 1, 427 to 7, 030 per correct diagnosis gained compared with TE. The model was sensitive to the sensitivity and specificity of TE and the prevalence of fibrosis. CONCLUSIONS: TE is an accurate diagnostic method in patients with moderate fibrosis or cirrhosis. TE is less effective but less expensive than liver biopsy. Systemic implementation of TE should be considered for the noninvasive assessment of liver fibrosis.